Incremental Cost Analysis of Training of Trainers and Helpers in Problem Management Plus (PM+) Using an Ensuring Quality in Psychological Support (EQUIP) Competency-based Approach in Nepal - Gloria A. Pedersen; Niko C. Gautam; Kriti Pudasaini; Nagendra P. Luitel; Michael W. Long; Alison Schafer; Brandon A. Kohrt (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas)
We estimated incremental costs of a competency-based Problem Management Plus (PM+) training of trainers (ToT) and training of helpers (TOH), guided by the World Health Organization (WHO)/United Nations International Children’s Emergency Fund (UNICEF) Ensuring Quality in Psychological Support (EQUIP) platform compared to a standard PM+ training. Activity-based cost analysis was conducted in Kathmandu, Nepal from July to October 2021. Organisational perspectives were assessed on resources required to implement one PM+ ToT, one EQUIP training for trainers and six PM+ ToH. For PM+ trainers, a standard PM+ ToT costs NPR 63,800.06 (US$510.40), with additional training on EQUIP competency-based approaches and digital platform costing an incremental NPR 45,111.15 (US$360.89). A standard PM+ helper training costs an average of NPR 207,906.35 (US$1,663.25) compared to an EQUIP-based PM+ ToH costing NPR 211,122.71 (US$1,688.98), for an incremental NPR 3,216 (US$25.73) per ToH. An EQUIP competency-based approach requires initial investment through training of PM+ trainers; thenceforth, differences in time and costs are negligible for training PM+ helpers when using an EQUIP approach compared to a standard approach. Given minimal cost differences and potential benefits for improving provider competency and client safety and outcomes, we recommend greater use of EQUIP. Stakeholders may use this study as a guide for costing competency-based approaches.